Containing COVID‐19 risk in the UAE: Mass quarantine, mental health, and implications for crisis management. Issue 1 (13th September 2021) - Thomas, Justin; Terry, James P.
Abstract: The COVID‐19 pandemic is the first global "NASECH disaster, " owing to its natural hazard (NH) origin and unprecedented subsequent repercussions for global society (S), economy (EC), and health (H). Emergency health control measures required the implementation of compulsory mass quarantine (CMQ) or so‐called periods of "lockdown." Yet, CMQ is an instrument with iatrogenic consequences, associated with a rise in societal levels of depression, anxiety, and posttraumatic stress. With a view to informing future crisis management, the study investigated sociodemographic factors associated with mental wellbeing during the March–April 2020 lockdown in the United Arab Emirates. Respondents ( n  = 1585) completed self‐report measures of depression (PHQ8) and generalized anxiety (GAD7). Rates of symptomatology were notably higher than those observed in similar UAE‐based studies before the pandemic. Younger age, urban‐dwelling, female‐gender, and a history of mental health problems were significant factors linked to elevated levels of depression and anxiety. Findings emphasize (1) the crucial need for psychological intervention after disasters and (2) the importance of strengthening the nexus at the intersection of public health and disaster risk reduction (DRR). Implications are that future pandemic containment would benefit from adopting new Health–DRR paradigms and ensuring these are effectively translated into disaster policy. 摘要: 新冠肺炎大流行是全球首个"NASECH灾害"，这归因于其自然灾害（NH）来源和对全球社会（S）、经济(EC)和卫生(H)造成的前所未有的后续影响。紧急卫生控制措施要求执行强制集中隔离（CMQ）或所谓的"封城"。不过，作为一项工具，CMQ具有医源性结果，后者与抑郁、焦虑和创伤后压力的社会层面的恶化相关。为对未来危机管理作贡献，本研究调查了2020年3月至4月封城期间与阿联酋地区居民的精神健康相关的社会‐人口统计因素。调查对象（n = 1585）完成了抑郁症（PHQ8）和一般化焦虑（GAD7）的自测衡量。症状率显著高于大流行前在类似研究（基于阿联酋）中得出的结果。与抑郁症和焦虑程度上升相关的显著因素包括年龄较小、居住在城市、女性以及精神健康问题史。研究发现强调了（1）在灾后进行心理干预（PIAD）这一关键需求；（2）强调公共卫生和灾害风险减少（DRR）二者之间复杂关系的重要性。得出的意义：采纳新的卫生‐DRR范式和确保范式有效转化为灾害政策，将有益于未来大流行的响应措施。 Resumen: La pandemia de COVID‐19 es el primer "desastre NASECH" mundial, debido a su origen de peligros naturales (NH) y las repercusiones posteriores sin precedentes para la sociedad (S), la economía (CE) y la salud (H) globales. Las medidas de control de la salud de emergencia requirieron la implementación de cuarentena masiva obligatoria (CMQ), o los llamados períodos de "bloqueo". Sin embargo, CMQ es un instrumento con consecuencias iatrogénicas, asociadas con un aumento en los niveles sociales de depresión, ansiedad y estrés postraumático. Con miras a informar la futura gestión de crisis, el estudio investigó los factores sociodemográficos asociados con el bienestar mental durante el cierre de marzo a abril de 2020 en los Emiratos Árabes Unidos. Los encuestados (n = 1585) completaron medidas de autoinforme de depresión (PHQ8) y ansiedad generalizada (GAD7). Las tasas de sintomatología fueron notablemente más altas que las observadas en estudios similares realizados en los Emiratos Árabes Unidos antes de la pandemia. La edad más joven, la vivienda urbana, el sexo femenino y un historial de problemas de salud mental fueron factores importantes relacionados con niveles elevados de depresión y ansiedad. Los hallazgos enfatizan (1) la necesidad crucial de una intervención psicológica después de los desastres (PIAD) y (2) la importancia de fortalecer el nexo en la intersección de la salud pública y la reducción del riesgo de desastres (RRD). Las implicaciones son que la futura contención de una pandemia se beneficiaría de la adopción de nuevos paradigmas de salud y reducción del riesgo de desastres y de garantizar que estos se traduzcan efectivamente en políticas de desastres.